Geology And Change - Time-Life Books (Time-Life Books : Hong Kong, 1994)
A visually-driven introduction to geology and Earth's dynamic processes. Key topics include: Rock formation, plate tectonics, mountain building, erosion, and Earth's changing surface Evidence of geological change through deep time, such as fossils, strata, and landscape features Illustrated with photographs, diagrams, and charts to support the narrative
Keywords: Geology